PTSD symptoms and overt attention to contextualized emotional faces: Evidence from eye tracking. (November 2018) - Milanak, Melissa E.; Judah, Matt R.; Berenbaum, Howard; Kramer, Arthur F.; Neider, Mark
Highlights: Individuals with greater PTSD symptom severity are more easily distracted by non-relevant, potentially threatening stimuli. Individuals with greater severity of PTSD symptoms spend less time looking at uncomfortable, threat-related negative facial expressions such as fear and marginally disgust. PTSD symptoms may relate to greater attention toward non-facial background scenes and less attention toward facial stimuli, especially when conveying a fear or disgust expression. Abstract: Abnormal patterns of attention to emotional faces and images are proposed by theories of posttraumatic stress disorder (PTSD), and this has been demonstrated empirically. However, few studies have examined how PTSD symptoms are associated with attention to emotional faces in the context of emotional background images. Eye tracking data were collected from seventy-eight undergraduates with a history of experiencing at least one traumatic event as they completed the Contextual Recognition of Affective Faces Task (CRAFT; Milanak and Berenbaum, 2014), which requires subjects to identify the emotion depicted by faces superimposed on an emotional background image. Greater PTSD symptom severity was associated with more time spent looking at background contexts and less time looking at target faces. This is consistent with greater susceptibility to distraction by task-irrelevant emotional stimuli. The duration of each gaze fixation upon fear faces was shorter for those with greater PTSD symptoms, and this pattern was marginally significant for disgust faces. These findings suggest that PTSD symptoms may relate to greater attention toward non-facial background scenes and less attention toward facial stimuli, especially when conveying a fear or disgust expression.